Pengaruh Implementasi Pembelajaran Berdiferensiasi pada Pemenuhan Kebutuhan Belajar Peserta Didik Tingkat Sekolah Dasar - Pebriyanti, Diantika (Jurnal Kridatama Sains dan Teknologi, 2023)
A learning innovation is needed that can increase students' learning motivation because of differences in their learning needs. A learning innovation called differentiated learning tries to meet the learning needs of diverse students. The purpose of this study is to describe how the application of differentiated learning has an impact on meeting the learning needs of students in elementary schools which can be seen from the increase in learning outcomes, the involvement of students in learning, and the ability to think critically of students while learning. The research technique used is known as literature review, used to collect information or sources about a particular subject and can be accessed from various sources, including journals, books, the internet, and other literature. Fulfillment of these learning needs can be seen from various aspects, such as learning readiness which refers to the ability of students to accept new material, a strong interest or desire from students with the potential they want to develop, as well as the profile of students who are influenced by learning styles, level cognitive, cultural background, and so on. According to a number of scientific journals and articles that the authors have examined, varied learning has an impact on how well students achieve their learning needs. When differentiated learning is used, students' learning outcomes improve as a result of meeting their needs and increasing their willingness to learn while engaging in the learning process.Keywords: differentiated learning, learning needs, students